PARTISIPASI POLITIK PEREMPUAN PADA PEMILIHAN KEPALA DAERAH (PILKADA) KABUPATEN BENGKALIS TAHUN 2020 - Nurul Fatma; Tito Handoko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Political participation is essentially a measure to determine the quality of a citizen's ability to interpret a number of symbols of power into personal symbols. Women are often seen as second-class creatures who prioritize feelings, so that their participation in politics is predicted to have poor performance. However, feminism is increasingly aware of the importance of equality between men and women in every aspect of life, including in politics. This awareness emerged as a driving force for women to actively participate in politics. There are various factors that affect women's political participation in participating to join politics both as voters and elected people. The problem in this study is to find out the factors that influence women's political participation in the 2020 election for the Regional Head of the Regent and Deputy Regent of Bengkalis Regency. This research method is qualitative with descriptive analysis. Collecting data using interviews and documentation. This research was conducted in Bengkalis Regency. The result of this study is that participation results show an increase in the number of women's political participation in the 2020 Regional Head Elections (Pilkada) in Bengkalis Regency. Of the 3 indicators of factors that influence women's political participation as follows: (1) sociological factors, through aspects of religion, gender/gender equality, ethnicity, social class, place of residence, employment and education, the dominant background is gender equality as a driving force women's community to vote for female candidates. (2) economic and rational factors, there is a political dowry that is carried out by the candidate and his successful team to attract the hearts of prospective female voters in exercising their voting rights. (3) psychological factors, through aspects of political trust, trust in candidates, trust in issues and political awareness, factors that greatly influence women's political participation, namely from the aspect of political awareness through the encouragement and strategy carried out by the Bengkalis Regency KPU. Keyword: Political participation, Women's politics, Local elections